Ultrasound-Based Prognostic Anatomical Parameters for Post-Prostatectomy Incontinence: A Systematic Review - Cecile T. Pham; Jordan E. Cohen; Manish I. Patel (Société Internationale d’Urologie Journal)
Background: A number of assessment methods for the pelvic floor have been described. Male pelvic floor ultrasound is an accessible, noninvasive assessment tool. Objective: To evaluate current published literature on anatomical parameters on pre- and postoperative ultrasound imaging of the male pelvic floor and correlation with continence status following radical prostatectomy (RP). Methods: A comprehensive literature search was conducted using the PRISMA guidelines to identify publications up to November 2022. Exclusion criteria consisted of animal studies, non-English articles, case reports, reviews and abstracts or reports from conferences. A full-text review was performed on 12 papers using ultrasound to assess pelvic floor anatomy and correlation with continence status following RP. Results: A total of 18 anatomical parameters were evaluated using US. Membranous urethral length (MUL), striated urethral sphincter (SUS) morphology and activation were most commonly studied. Shorter pre- and postoperative MUL, decreased preoperative SUS thickness and vascularity, postoperative discontinuity of SUS muscle fibres and decreased SUS activation are associated with post-prostatectomy incontinence (PPI). There is a paucity of data comparing anatomical changes in men prior to and following RP. The benefits of transperineal ultrasound are that it is minimally invasive, accessible, provides dynamic imaging of all three striated muscle complexes simultaneously and includes a bony landmark to reference measures of pelvic floor muscle displacement. Conclusions: Ultrasound evaluation of the male pelvic floor is an evolving field as there is development in technology and understanding of pelvic floor anatomy. It is an accessible and dynamic imaging modality, which allows both morphological and functional assessment of pelvic floor anatomy and its role in PPI. MUL and SUS morphology and activation are associated with continence status following RP. Several other anatomical parameters that may predict PPI were identified. Current literature is limited by small, single-centre studies with heterogeneous cohorts and methodologies.